EXPLORING THE POTENTIAL OF NATURAL PARKS IN THE PROCESS OF RENOVATION OF MATURE COASTAL TOURIST DESTINATIONS: EVIDENCE FROM THE VALENCIA REGION IN SPAIN - Frías, Margarita Capdepón; Sánchez, Isabel Rodríguez; Climent, María Paz Such (Tourism & Management Studies, 2012)
The renovation of coastal destinations characterized by a standard and mature tourist offer is a key subject that compromises the future of this important socioeconomic activity and thus the analysis of possible strategies focused on the improvement of the offer is essential. This paper focuses on the use of natural heritage to create tourist products in the mature destinations of the Valencia region based on the enhancement of natural parks. With this aim, other experiences have been analyzed where protected natural areas have been incorporated to the renovation process of some main mature destinations on the Mediterranean coast. In a final stage, the natural parks’ potential to be incorporated into the tourist offer has been explored and then contrasted with the opinions of the managers responsible for these protected areas. The work has contributed to check the willingness of the environmental public entities to make a better use of the natural parks with a tourist scope and on the other hand to know the managers’ opinion about the parks current level of use. The paper concludes that the natural parks of the Valencia region have a great natural and cultural heritage which has been underestimated and a potential that needs to be considered; even though these natural areas still present a limited tourist use, there is a growing development of recreational activities that complement the traditional tourist offer of coastal destinations.